Evaluation of the level of development of sport tourism China and Europe - Wu Linna; Vitalii Brusentsev (Слобожанський науково-спортивний вісник, 2014)
Purpose: to evaluate the level of development of sport tourism China and Europe. Material and Methods: analysis and generalization of literature and electronic sources, official web-sites. Results: a significant increase in the number of tourists in recent years. The level of development of sport tourism is constantly growing and shows mass popularity among the population. Conclusions: the development of sport tourism in Europe more than in China. Improvement of forms of organization and means of sport tourism will attract more people.